Design and Analysis of a Knowledge Management System for Sawit Seberang Health Center Using the Inukshuk Methodology - Nurainun Syahdia; Ilka Zufria (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2024)
The Sawit Seberang Health Center as the technical implementation unit of the health service is responsible for carrying out health development in the Sawit Seberang area, both in terms of health services and providing health knowledge that is useful for medical personnel in particular and the community in general. The problem faced by the Community Health Center is the unavailability of a computer-based system that can be accessed online as a medium for storing and sharing knowledge and information about health, both knowledge for fellow medical personnel and knowledge for the community. This problem can be solved with the KMS application which can be accessed online. The method used is the Inukshuk KM Model Method. The Inukshuk Knowledge Management model is a framework that has been refined from the SECI model (socialization, externalization, combination and internalization) with the addition of components such as leadership, culture and technology. The relationship with Knowledge Management is that it can provide information about Tacit and Explicit Knowledge in the organization. The result of this research is the KMS Puskesmas application which can be accessed online as a medium for storing and sharing knowledge for fellow medical personnel as well as a medium for information and knowledge for the community.